Vision and Verticality A Multidisciplinary Approach - Zuev, D.; Bratchford, G. (2024)
This rich and accessible volume maps current debates within the expanded field of image-based, vertical analysis. With contributions from astronauts, artists, architects, sociologists, urbanists, visual culture theorists, geographers, anthropologists and more the book signals new moves in inter and multidisciplinary research on visual-vertical thinking and related practices within the social sciences, humanities and across the arts. Grounded in socio-visual thinking, Vision and Verticality addresses the emerging shift in the way social scientists move from a sociology of or through images towards a sociology with images. In doing so, this volume illustrates how the sky and atmosphere remain a surprisingly underexplored domain within visual sociology, beyond the framework of drone-related research. Finally, this volume asserts how vertical and atmospherically framed socio-visual analysis is beginning to shape and inform how we see and experience urban spaces, travel, leisure, politics, and environmental challenges through various prisms, including artistic practices, methodological processes, and user-generated content.